ANALISIS IMPLEMENTASI PROGRAM DUKCAPIL SMART SEBAGAI INOVASI PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANTUL - Ikhsan Adit Setyawan; Agustina Rahmawati (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2023)
In the current New Normal Era due to COVID-19, Bantul Regency has also increased the use of information technology for public service innovation, one of which is the use of the Dukcapil Smart Application. The implementation of the program requires a study to improve the quality of the results that will be achieved later from the implementation of these public service innovations, as well as to provide an overview of the Population and Civil Registration Service so that it can assess the readiness of the factors that need to be considered when implementing policies related to the Dukcapil Smart innovation policy. The concept of Policy Implementation put forward by Mazmanian and Sabatier became a reference in making this scientific work. This research uses a descriptive qualitative method, the focus of the research is located in Disdukcapil Bantul Regency.